Indian feminisms: Law, Patriachies and violence in India - Gangoli, Geetanjali (London Routledge, 2020)
Contributing to debates on feminism, this book considers the impact made by feminists in India from the 1970s. Geetanjali Gangoli analyses feminist campaigns on issues of violence and women$1 (Bs rights, and debates on ways in which feminist legal debates may be limiting for women and based on exclusionary concepts such as citizenship. She addresses campaigns ranging from domestic violence, rape, pornography and son preference and sets them within a wider analysis of the position of women within the Indian state.s